VALUES AND TYPES OF VALUES, ATTITUDES AND COMPONENTS OF ATTITUDES, JOB SATISFACTION AND DIMENSIONS OF JOB SATISFACTION - Abidin Nasyar; Zakaria Syafei; Eka Sri Mulyani; Rijal Firdaos; Rasad Mulyadi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
This study aims to examine the relationship between values, attitudes, and job satisfaction in organizational behavior within the context of Islamic education management. This study is motivated by the importance of understanding the psychological factors that influence individual performance in educational organizations. The method used is a qualitative approach through library research with content analysis of various scientific literature sources. The results of the study indicate that values shape attitudes, and attitudes significantly influence job satisfaction. The integration of these three aspects, particularly with Islamic values, contributes to improving performance, the quality of education, and creating a harmonious and sustainable organizational environment.